Peace Child : Imagine Sharing the Gospel With Cannibals Who Admire Judas's Betrayal More Than Jesus' Sacrifice - Richardson, Don (Seattle Ywam Publishing, 2003)
Among the headhunting Sawi of Irian Jaya, treachery was an ideal that generations of their people had perfected ... When missionaries, Don and Carol Richardson searched for the key that would open the gospel to the Sawi, God moved in a stunning way. He revealed his true Peace Child ... [This book] chronicles the agony - and the triumph -- of the Richardsons' unforgettable sojourn among this people loved by God.
Include Illustration
Keywords: Sawi (Indonesian people)--Missions -- Sawi (Indonesian people) -- Indonesia